A benign helminth alters the host immune system and the gut microbiota in a rat model system - Wegener Parfrey, Laura; Jirků, Milan; Šíma, Radek; Jalovecká, Marie; Sak, Bohumil; Grigore, Karina; Jirků Pomajbíková, Kateřina (PloS one, 2017)
Helminths and bacteria are major players in the mammalian gut ecosystem and each influences the host immune system and health. Declines in helminth prevalence and bacterial diversity appear to play a role in the dramatic rise of immune mediated inflammatory diseases (IMIDs) in western populations. Helminths are potent modulators of immune system and their reintroduction is a promising therapeutic avenue for IMIDs. However, the introduction of helminths represents a disturbance for the host and it is important to understand the impact of helminth reintroduction on the host, including the immune system and gut microbiome. We tested the impact of a benign tapeworm, Hymenolepis diminuta, in a rat model system. We find that H. diminuta infection results in increased interleukin 10 gene expression in the beginning of the prepatent period, consistent with induction of a type 2 immune response. We also find induction of humoral immunity during the patent period, shown here by increased IgA in feces. Further, we see an immuno-modulatory effect in the small intestine and spleen in patent period, as measured by reductions in tissue immune cells. We observed shifts in microbiota community composition during the patent period (beta-diversity) in response to H. diminuta infection. However, these compositional changes appear to be minor; they occur within families and genera common to both treatment groups. There was no change in alpha diversity. Hymenolepis diminuta is a promising model for helminth therapy because it establishes long-term, stable colonization in rats and modulates the immune system without causing bacterial dysbiosis. These results suggest that the goal of engineering a therapeutic helminth that can safely manipulate the mammalian immune system without disrupting the rest of the gut ecosystem is in reach.
Keywords: Feces; Rats; střevní mikroflóra; Intestines; Bacteria; biodiverzita; Gene Expression Regulation; Rats, Wistar; interleukin-10; Gastrointestinal Microbiome; krysa rodu Rattus; imunitní systém; slezina; Hymenolepis diminuta; střeva; regulace genové exprese; Immunoglobulin A; Models, Biological; ženské pohlaví; zvířata; feces; fylogeneze; Host-Parasite Interactions; imunoglobulin A; biologické modely; Biodiversity; Immune System; interakce hostitele a parazita; potkani Wistar; Interleukin-10; Female; Phylogeny; Spleen; Animals